One‐Step Synthesis of NiMn‐Layered Double Hydroxide Nanosheets Efficient for Water Oxidation. Issue 1 (2nd November 2018) - Li, Ruiqi; Liu, Yuqian; Li, Haobo; Zhang, Man; Lu, Yiran; Zhang, Lin; Xiao, Jianping; Boehm, Frank; Yan, Kai
Abstract: Layered double hydroxides (LDHs) are noble metal–free 2D materials promising for water oxidation. One‐step synthesis of ultrathin NiMn‐LDHs nanosheets is successfully achieved at room temperature avoiding the multiple tedious steps (e.g., hydrothermal treatment, exfoliation). The as‐prepared NiMn‐LDHs (1.3 nm thickness) exhibit the twofold enhancement of the activity and a reduction of overpotential by 80 mV at 10 mA cm −2 in comparison with the traditional NiMn‐LDHs in 0.1m NaOH, which is superior to the previously reported LDH‐derived electrocatalysts. The combination of theoretical and experimental results manifest that the largely enhanced electrocatalytic water oxidation activity of NiMn‐LDHs nanosheets is associated with the highly exposed active sites with a nearly optimal intermediates (*OH and *O) adsorption energy. Abstract : Ultrathin NiMn‐layered double hydroxides (LDHs) nanosheets are successfully fabricated in one step at room temperature without tedious hydrothermal treatment. Theoretical and experimental results manifest that the largely enhanced electrocatalytic activity of NiMn‐LDHs nanosheets is associated with the highly exposed active sites with a nearly optimal intermediates (*OH and *O) adsorption energy.